With or Without Nasal Continuous Positive Airway Pressure During Delayed Cord Clamping in Premature Infants <32 Weeks: A Randomized Controlled Trial Using an Intention-To-Treat Analysis - Deng, Rui; Wu, Yan; Xiao, Guiyuan; Zhong, Xiaoyun; Gong, Hua; Chen, Wen; Zhou, Ligang; Shen, Biao; Wang, Qi (Frontiers in Pediatrics, 2022)
Objective: To assess whether providing nCPAPduring delayed cord clamping is beneficial for very preterm births. Study design: A randomized and controlled study was performed from March 2020 to May 2021. Premature infants (below 32 weeks of gestational age) were allocated to receive at least 60 seconds of delayed cord clamping with nCPAP(DCC+nCPAP) or DCC only:without nCPAP.When the experiment was randomized to the DCC+nCPAP group, the ventilator HAMITON-C1 was used for noninvasive ventilation with the cord intact. For both groups, after the umbilical cord was clamped, the infants were carried immediately to the resuscitation room to continue receiving standard transition/ resuscitationResults: 147 infants were analyzed statistically. The median time for cord clamping was 60 seconds with IQR (60.00, 60.00 vs.60.00,70.00) in both groups. There was no significant statistical difference in the safety indicators between the two groups. These safety indicators include: the incidence rate of SpO2< 80% at 5 minutes after birth, HR < 100 bpm at 5 minutes after birth, rectum temperature < 36.0 ℃ at admission, maternal postpartum hemorrhage, maternal postpartum infection. There were no difference in the primary outcome of mechanical ventilation rate after admission within 24 hours of life (p=0.169). The blood gas pH at 1 h after birth was not different between groups, although the blood gas pH at 1 h after birh tended to be higher in DCC+nCPAP group(p = 0.069).Similarly, there was a trend for lower incidence of BPD in the DCC+nCPAP group (p = 0.064),but overall there was no difference between groups. There were no differences in the other outcomes concerning the transition of the infants, short-term neonatal outcomes, or short-term maternal outcomes.Conclusions: We have proved that delayed cord clamping with nCPAP in premature infants with gestational age < 32 weeks was feasible and safe. Although there was a trend toward a higher blood gas pH at 1 h after birth and a lower incidence of BPD in the DCC+nCPAP group,DCC+nCPAP did not result in a corresponding measurable clinical improvement, nor did it reduce subsequent neonatal morbidity. A larger multi-center study will be needed to evaluate the effect of DCC with nCPAP.